Soliton phenomena in the process of the functioning of the heart - Adamski, Adam (Journal of Cardiology and Cardiovascular Medicine, 2023)
The biochemical model explains the intricate mechanisms of psychobiological life. He still cannot explain what the transition from inanimate to living matter is all about. Where is the threshold and what is its essence, what role do biochemical processes play in the coherence of the soma with consciousness and its impact on the soma and vice versa? A similar problem is with other mental processes, their nature does not fit into the biochemical model of life and is inexplicable on the basis of biochemical interactions, again it is much easier to describe it in the light of quantum processes - including wave physics. It is similar to the functioning of the heart or other organs, where only the biochemical processes of the cell are considered, ignoring the bioelectronic processes. Man is not only a purely biological construct but also contains the basis of biochemical, bioelectronic, information, and cybernetic processes that are responsible for shaping the psychobiological processes of man. Contemporary biosystems in science are considered at the level of corpuscular structures, ignoring energy and information structures. By shifting the cognitive emphasis towards energy and information structures, the organism can be perceived as a quantum generator of information: electromagnetic, soliton, acoustic, spin and bioplasma. This bioelectronic construction creates homo electronics with his electronic personality.